Structural Organizations of Qβ and MS2 Phages Affect Capsid Protein Modifications by Oxidants Hypochlorous Acid and Peroxynitrite - Bastin, Guillaume; Loison, Pauline; Vernex-Loset, Lionel; Dupire, François; Challant, Julie; Majou, Didier; Boudaud, Nicolas; Krier, Gabriel; Gantzer, Christophe (Frontiers in Microbiology, 2020)
Pathogenic enteric viruses and bacteriophages such as Qβ and MS2 are transmitted through the fecal-oral route. [However,] lien entre l’idée précédente et celle à venir? la transition ne me semble pas adaptée oxidants such as peroxynitrite (ONOOH) and hypochlorous acid (HClO) can prevent new infection by inactivating infectious viruses. Their virucidal effect is well recognized, and yet predicting the effects of [oxidants] tous les “oxidants” ou juste ONOOH et HClO? on viruses is currently impossible because the detailed mechanisms of viral inactivation remain unclear. Our data show that ONOOH and HClO cross-linked the capsid proteins and RNA genomes of Qβ and MS2 phages. Consistently, the capsids appeared intact by transmission electron microscopy (TEM) even when 99% of the phages were inactivated by oxidation. Moreover, a precise molecular study of the capsid proteins shows that ONOOH and HClO preferentially targeted capsid protein regions containing the oxidant-sensitive amino acid C, Y, or W. Interestingly, the interaction of these amino acids was a crucial parameter defining whether they would be modified by the addition of O, Cl, or NO2 or whether it induced the loss of the protein region detected by mass spectrometry, together suggesting potential sites for cross-link formation. Together, these data show that HClO and ONOOH consistently target oxidant-sensitive amino acids regardless of the structural organization of Qβ and MS2, even though the phenotypes change as a function of the interaction with adjacent proteins/RNA. These data also indicate a potential novel mechanism of viral inactivation in which cross-linking may impair infectivity.